Digital marketing strategy for hospitals in the post Covid-19 pandemic in 2023: A literature review - Astriana Astriana; Wahyu Sulistiadi (Malahayati International Journal of Nursing and Health Science, 2024)
Background: The healthcare industry is currently facing significant pressure due to the emergence of Covid-19. The Covid-19 pandemic has had adverse effects on the global economy, industries, and organizations, impacting marketing strategies and expenditures. Due to total lockdown in various regions, digital marketing has become crucial as traditional marketing strategies are no longer effective. One way to gain a competitive edge is to develop an effective marketing strategy. The goal is to inform the public about hospitals, provide information about the facilities and services offered, and build a positive image through the trust of the community.Purpose: To find out the digital marketing strategies in hospitals in the post-Covid-19 pandemic.Method: This study was conducted descriptively with a literature review approach. The search was carried out on articles published in English and Indonesian from 2014 to 2022 using Google Scholar, with keywords such as "digital marketing, hospitals, and Covid-19 pandemic."Results: Hospitals need to implement effective digital marketing to promote medical care services, expand business, and ensure patient satisfaction while maintaining quality healthcare services. Social media is a widely used digital marketing platform for healthcare facilities. The use of digital marketing can be applied to promote hospital services and strengthen the brand image of healthcare facilities.Conclusion: Digital marketing can be implemented through various options, either through applications designed by hospitals personally or through various other methods such as Search Engine Marketing (SEM), Email Marketing, Search Engine Optimization (SEO), social media, display advertising, referral marketing, affiliate marketing, content marketing, online advertising, and viral marketing.